Rituximab in combination with adapted-dose of ifosfamide and etoposide as salvage treatment in elderly refractory/relapsed diffuse large B-cell lymphoma patients non-candidate for high dose therapy: a retrospective study. Issue 3 (23rd February 2022) - Aussedat, Guillaume; Maucort-Boulch, Delphine; Rey, Philippe; Safar, Violaine; Karlin, Lionel; Elsensohn, Mad Helenie; Bachy, Emmanuel; Lebras, Laure; Favier, Bertrand; Vantard, Nicolas; Ghergus, Dana; Golfier, Camille; et al.
Abstract: We retrospectively reviewed for 72 relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL) patients ineligible for autologous stem-cell transplantation (ASCT) treated between 2004 and 2017, efficacy and safety profile of rituximab (375 mg/m 2 ) in combination with etoposide (300 mg/m 2 ) and ifosfamide (1500 mg/m 2 ) at 2, 3, or 4-week intervals. Median age was 79 years (range, 64–92). The median number of previous line was 1 (range 1–8). Patients received a median of six cycles (1–12). Fourteen patients (19%) presented partial and 14 complete responses (19%). Among the 369 cycles, nine patients developed febrile neutropenia (13%), 14 a grade 3–4 neutropenia (19%), 7 a grade 3–4 thrombocytopenia (10%) without grade 3–4 non-hematological toxicity. With a median follow up of 7.8 months, the median progression-free survival, overall survival, and duration of response were 4.4 months, 9.4 months, and 12 months, respectively. This regimen represents a therapeutic option in R/R DLBCL patients ineligible to ASCT.